Assessment of Factors Affecting Telebirr (Mobile Money) Project Implementation in the Case of Ethio Telecom Sector - Memar Belete Asires; Arvinder Singh Chawla (International Journal of Mobile Computing Technology, 2025)
Background: Mobile money services facilitate financial transactions through mobile devices, reducing dependence on physical cash and promoting financial inclusion. The Telebirr Mobile Money project by Ethio Telecom is a key initiative in this domain. Objective: This study aims to examine the factors influencing the successful implementation of the Telebirr Mobile Money project within Ethio Telecom. Methods: A census survey was conducted among 75 project team employees at the Lebu and Ayertena branch offices. Data were collected via a 5-point Likert scale questionnaire and supplemented with interviews of the project manager. Descriptive statistical analysis, including frequencies, percentages, means, and standard deviations, was performed using SPSS software. Findings: Among the factors assessed, Financial Regulation, Technology, and Compatibility, “Technology Feedback” scored the highest mean value (m=3.77), indicating that the platform is well-designed to respond to user behavior and environmental conditions. However, issues were identified related to the flexibility of API integration with third-party systems.Contribution: This study provides empirical insights into the critical technological and regulatory factors affecting mobile money project implementation in Ethiopia, highlighting the importance of adaptive platform design.Recommendation: To enhance system interoperability, it is recommended that Telebirr improves its API development to support greater flexibility for integration with third-party applications.
Keywords: Ethio telecom; Telebirr; compatibility; project implementation; technology